Mediazione e responsabilità, nel suono - Di Scipio, Agostino (Musica/Tecnologia, 2010)
Agostino Di Scipio, questioning the relationship between music, technology and society, points to the need of abandoning a strictly sociological point of view in favor of an approach that considers the actions and decisions mediated through technology – together with the responsibility the composer assumes on these processes of mediation – in their capacity to trace elements capable to be audible within the conditions of existence of sound and music. Through a series of steps – which go from a hermeneutic of technology to the identification of paradigms of mediation, from the definition of the conditions for responsibility, to the assessment of the nature of the plurality of tracks left in the sound from the constructive gesture – the author points out the terms of a perspective informed to the creative practice, the conditions and the techniques of those who act in a creative sense. In a world structured as a network of interconnected technical systems, the reflection must be brought from the aesthetic plane to the more decisive one of ‘responsibility of the media’, where “the skills and awareness that a musician has of the technologies of his work are not secondary to the meaning and significance of the final products of his work”.